Stochastic Integrals and Power Contractions in Bernoulli Selections (Journal of Informatics and Mathematical Sciences, 2018)
Random contractions and Bernoulli selections are recognized as strong analytical tools of probability distributions theory. The paper investigates the distribution of a Bernoulli selection incorporating a stochastic integral and a random contraction. Moreover, the paper establishes a practical interpretation of the formulated Bernoulli selection.
Keywords: Stochastic integral; Random contraction; Bernoulli selection